Massive ovarian edema with fallopian tube torsion treated with transumbilical laparoendoscopic single-site surgery: a case report - Mu, Dan; Shen, Yangmei; Chen, Yali (Frontiers in Oncology, 2025)
Massive ovarian edema (MOE) is a rare benign condition that can occur at any age, and mainly affects women of childbearing age and prepubertal girls. Patients with MOE do not have specific signs and symptoms, and imaging may show cystic or solid masses. Therefore, it is often unclear preoperatively whether the mass is a benign or malignant ovarian tumor. This increases the possibility of salpingo-oophorectomy due to suspicion of malignancy which, in turn, affects the fertility of young women and alters their sex hormone levels. We report the case of a 14-year-old girl with three complete turns of torsion of both the right fallopian tube and right ovary, and enlargement of the right ovary without necrosis. We performed transumbilical laparoendoscopic single-site surgery (TU-LESS) for diagnosis and treatment. During surgery, an ovarian cyst was removed and sent for frozen section, revealing MOE. Fertility-sparing surgery was therefore performed and the affected ovary was suspended to prevent further torsion.